Unveiling the immunometabolic landscape of colorectal cancer through PANoptosis-related gene expression - He, Xiaoyu; Wang, Wenhao; Li, Li; Yin, Yiru; Ding, Shunbin (Frontiers in Immunology, 2026)
BackgroundColorectal cancer (CRC) development and progression are linked to genetic factors, environmental influences, and dysregulated signaling pathways.MethodsThe differentially expressed pan-apoptotic genes (CPAN_DEGs) between CRC and normal colon tissues were screened from bulk RNA-sequencing (RNA-Seq) datasets. The putative biological functions of these CPAN_DEGs were explored through functional enrichment analysis and the protein-protein interaction (PI) network. Unsupervised clustering was used to stratify patients on the basis of CPAN_DEGs, and a prognostic model was constructed using LASSO dimensionality reduction. Based on the CPAN-index score, the patients were divided into the high-risk and low-risk groups, and the survival rates and immunophenotypes were compared. The predictive performance of the CPAN-index model was confirmed in an external validation set. The expression patterns of PANoptosis genes across different cell types in CRC samples, and the distribution of CPAN-index-positive cells within each subpopulation were analyzed using single cell RNA-Seq (scRNA-Seq) datasets. The expression of CDKN2A was confirmed in CRC cell lines, and its functional role was evaluated by gene knockdown.ResultsThe expression levels of PANoptosis-related genes showed significant heterogeneity across CRC samples, and the highest percentage (87.4%) was that of apoptosis-related genes. The differentially expressed genes (DEGs) between the CRC and normal tissue samples were significantly enriched in pathways related to metabolism and immune regulation. The CPAN-index constructed using 11 CPAN_DEGs effectively distinguished CRC patients in to the high-risk and low-risk groups, and the high-risk group showed an “invasion-metabolism-immunosuppressive” phenotype, along with immune tolerance and non-classical immune escape. The CPAN-index gene CDKN2A was upregulated in the CRC cell lines, and knocking down the CDKN2A gene inhibited their proliferation and promoted apoptosis in vitro. ScRNA-Seq data revealed a higher proportion of CPAN-index-positive immune cells, and a lower proportion of tumor cells positive for CPAN-index, thus underscoring its critical role in the tumor immune microenvironment.ConclusionsCDKN2A-mediated PANoptosis signaling network drives CRC progression by reshaping the immune microenvironment and metabolic reprogramming. The CPAN-index provides a new tool for accurate risk stratification of CRC patients, and suggests potential therapeutic strategies targeting the immunometabolism-death interaction network.